Strategi manajemen sumber daya, sistem bagi hasil, dan adopsi teknologi pada lembaga keuangan syariah: Untuk meningkatkan efisiensi dan kepuasan nasabah - alhadid, chealshe oliviana fega (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze resource management strategies, profit-sharing systems, and technology implementation in Islamic financial institutions to improve operational efficiency and customer satisfaction. Professional and competent human resource management is key to ensuring fast, accurate, and sharia-compliant services. The implementation of fair and transparent profit-sharing systems, such as mudharabah and musyarakah contracts, increases customer trust and creates financial efficiency. Furthermore, adopting digital technology, including mobile banking and sharia-based information systems, accelerates service delivery and strengthens transaction transparency, thereby enhancing customer satisfaction. This study uses a qualitative descriptive approach with a literature review and comparative analysis of the practices of Islamic financial institutions in Indonesia. The results indicate that the simultaneous integration of these three strategies can improve institutional performance, process efficiency, and customer loyalty. This study also emphasizes the importance of technological innovation and human resource capacity development as part of a sustainable management strategy. These findings align with international literature on digital transformation and management strategies in Islamic banking.